MICROSTRUCTURE AND HARDNESS PROFILE OF DISSIMILAR LAP JOINT OF TYPE 304 STAINLESS STEEL TO SS400 CARBON STEEL - Herry Oktadinata; Adi Ganda Putra (Balai Besar Logam dan Mesin, 2019)
Dissimilar metal welds between austenitic stainless steel and carbon steel are commonly used in oil and gas industries for certain reasons. The objective of this research is to asses the effect of filler metal and shielding gas on the microstructure and hardness of dissimilar lap joint of type 304 austenitic stainless steel to JIS SS400 low carbon steel. For the purpose of this investigation, the weldments were produced using flux-cored arc welding (FCAW). Three types of filler metals (E316L, E309L and E308L) and two different gas compositions (100%CO2 and 90%Ar+10%CO2) were selected to be used. Each of the weldments were analyzed on the microstructure characteristic and hardness profile of base metal (BM), heat affected zone (HAZ) and weld metal (WM) using optical microscope and microhardness Vickers. The metallographic examination revealed HAZ-SS400 contains martensites. Both HAZ-304 and WM show austenitic microstructure, with columnar and cellular sub-structures present at WM. The hardness profile of HAZ-304 is higher than BM-304, it may be attributed to the presence of the fine grains in HAZ-304 due to high temperature during welding. The hardness profile of WM-E309L exhibited the hardness from HAZ to WM tend to decrease linearly, while WM-E316L and WM-E308L showed the hardness from HAZ to WM also decreased but drastically dropped at fusion line (FL). The welds using E309L offer the best result in the point of view homogeneity of the hardness profile.